LEARNING OF IMLA’ USING FLASHCARDS ON WRITING SKILL AT ISLAMIC ELEMENTARY SCHOOL LEVEL IN SAMARINDA - Pimada, Luluk Humairo; Toba, Rostanti; Rasyidi, Abdul Wahab (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
There are some language skills, one of them is writing which has the steps of learning a foreign language. Writing skill has the most difficult skill. The use of instructional media has functions to facilitate teaching and learning activities, especially in Arabic learning of Imla? material. The flashcard is used as a medium to facilitate teaching and learning activities of Imla? for non-Arabic students. This research aimed to describe learning of Imla? on Arabic writing skill and describe learning implementation of Imla? on Arabic through flashcard at the level of elementary school at Elementary School level in Samarinda. The researcher used research design of qualitative descriptive by using the research instruments of observation, interview, and documentation. The research result obtained through the data sources from the principal, vice principal of curriculum, Arabic teachers and students. To analyze the data, the researcher used Miles and Huberman?s theory through three steps of data reduction, data display, and verification. The research results were that Arabic learning based on the writing skill on the elementary level included in category of Imla? manqul which is aimed for students to be able to recognize, know, and rewrite letters of Hijaiyah by the rules of writing and letters written separated or connected with other letters. The students were also able to recognize the meaning of what they wrote through flashcard. The use of flashcard was helpful in the Arabic teaching process, because the students were easier in understanding the meaning of each vocabulary they wrote. The students did not feel saturated in teaching and learning proses, because flashcard can be used by the students as a form of game which they usually play such as picture card. Therefore, the Arabic writing skill on the elementary level will be easier to be learnt by the students.